Superhydrophobic/Superoleophilic: Robust, Easy‐Cleaning Superhydrophobic/Superoleophilic Copper Meshes for Oil/Water Separation under Harsh Conditions (Adv. Mater. Interfaces 11/2019). Issue 11 (7th June 2019) - Pang, Bo; Liu, Huan; Liu, Peiwen; Zhang, Hua; Avramidis, Georg; Chen, Longquan; Deng, Xu; Viöl, Wolfgang; Zhang, Kai
Abstract : Robust and easy‐cleaning superhydrophobic and superoleophilic copper meshes are fabricated by introducing Cu(OH)2 nanoneedles or CuO nanoplates onto copper mesh surface via facile oxidation and subsequent coating with polydimethylsiloxane. Such copper meshes demonstrate high separation efficiency for mixtures of oils and diverse corrosive aqueous solutions or hot water. More details can be found in article number1900158 by Bo Pang, Kai Zhang, and co‐workers.